A Practical Gram-Scale Synthesis of Acrylohydroxamic Acid - Hamper, Bruce C.; Sullivan, Brendan T.; Rath, Nigam P.; Spilling, Christopher D. (Synthesis, 2017)
Acrylohydroxamic acid, which is a useful monomer for the preparation of polymeric materials, has been prepared in a straightforward, two-step synthesis from readily available starting materials. The key steps are coupling of acrylic acid with O-tetrahydropyranylhydroxyl amine to provide protection of the hydroxylamine functionality, followed by acid cleavage of the protecting group.
Keywords: hydroxamic acids; acrylohydroxamic acid; chelating agents; monomers; functionalized polymers; metal chelation